Testing the Consistency of G.H.A. Juynboll’s Determination of Common Link Narrators: An Analysis of the Encyclopedia of Canonical Hadith - Silfiani Silfiani; Abdul Hakim Wahid; Ummi Kalsum (STAI Publisistik Thawalib Jakarta, 2026)
Inconsistency in Juynboll’s classification of Common Link and Seeming Common Link narrators compared to his theory and classical evaluations. This study aims to examine the consistency of Juynboll’s identification of Common Link and Seeming Common Link narrators in his work. This study uses a qualitative library research approach with descriptive-analytical methods, analyzing isn?d reconstruction from the Encyclopedia of Canonical Hadith and supporting literature on rij?l al-?ad?th and jar? wa ta?d?l. The findings reveal that Juynboll’s application of the common link theory in the Encyclopedia of Canonical Hadith is not entirely consistent. Among the seven narrators examined, four narrators correspond to his classification of Common Link (CL) and Seeming Common Link (SCL) based on reconstructed isn?d transmission patterns. However, three narrators do not align with his criteria due to differences in transmission structures and their positions within sanad networks. Furthermore, several narrators classified by Juynboll as fabricators of hadith are considered trustworthy (thiqah) by classical scholars of jar? wa ta?d?l. These results indicate methodological inconsistencies and significant divergence between Orientalist approaches and classical Islamic hadith scholarship. Conclusion: Juynboll’s common link theory demonstrates inconsistencies in application, requiring reassessment through classical and isn?d-based analytical perspectives. This study contributes to critical hadith scholarship by evaluating Orientalist methodology and strengthening sanad-based analytical approaches in Islamic studies.